PETA KERAWANAN BANJIR SUB DAS CILUTUNG BERDASARKAN DATA GEOSPASIAL - Iing Nasihin; Dede Kosasih; Rahman Rahman (Jurnal Belantara, 2022)
A Flood is a natural phenomenon that causes material or non-material losses. The availability of geospatial information can be used to analyze the level of flood susceptibility. The purpose of this study was to identify and map flood-prone areas in the Cilutung sub-watershed based on geospatial data, namely land use and cover conditions, soil type, slope class, and rainfall. The method used in this study is weighting and scoring in geographic information systems (GIS). Based on the analysis, there are 4 classes of flood susceptibility in the Cilutung sub-watershed with the classification of safe, less vulnerable, moderate, and vulnerable. The distribution of flood-prone areas is almost spread over the entire Cilutung sub-watershed area, including the districts of Argapura, Banjaran, Bantarujeg, Cikijing, Cingambul, Lemahsugih, Maja, Majalengka, Malausma, Panyingkiran, Talaga, Cisitu, Jatigede, Jatigede, Tomo, and Wado. Medium class with an area of ​​22579 ha (36%), vulnerable class 18543 ha (30%), less vulnerable class 17883 ha (29%), safe class 2979 ha (5%). The most dominant parameters that cause flood vulnerability are flat slope 0-8%, latosol soil type, and land use in the form of rice fields, these parameters are spread in the southern and northern regions.